Rural Clusters in the Lublin Region (Eastern Poland)- Good Solutions for a Young Democracy - Barbara Szymoniuk (European Regional Science Association (ERSA), 2003)
Once Poland joins the European Union, competition in all sectors of economy, also in the sector of agriculture, will greatly intensify within the wider and more demanding market. It will then be necessary to compete by aggressive marketing techniques - both internationally and domestically. But the present level of competitiveness of Polish agriculture, which is based on small farms and backward compared to other European countries, is low. One of the means of improving this situation is integration of small farms. Worldwide evidence from the last few years shows that forming of local networks is an occasion to make connections between farms, small business and service, educational and self-governmental institutions, which is vital to improved effectiveness. It enables farmers to achieve extra profits and get a bigger market share, incorporating innovations in the field of production, services management and creating new local job opportunities. Such a local network of firms and institutions is called ?a cluster? or ?a local productive system?. Although ?clustering? as a concept or economic theory is unfamiliar to many people of Poland, when put into practice, it shows profitable results and a high level of achievement. This paper describes two types of clusters, already well developed in the Lublin Region, their short histories, goals, results and, eventually, their role in developing local democracy. Examples are derived from the rural sector, including the agricultural production industry (section 2.) and agritourism (section 3.). In section 4. threats and opportunities linked to the development of rural clusters in the region, are assessed. In the summary (section 5.) sample conclusions and recommendations that can lead to stimulation of the cluster formation as the means of creating new job opportunities and development of democracy in the rural areas, are given.
Keywords: 330